Evaluation of Ocular Complications in Intraoral Local Anesthesia - Rameet Sandhu; Vikas Sikarwar; Sushil Ojha; Dushyant Upadhyay; Anshdeep Singh; Shweta Sharma (Wolters Kluwer Medknow Publications, 2024)
Background: The most significant medications in dentistry are local anesthetics, and intraoral local anesthesia is arguably the most used dental procedure. However, complications have also been reported. Aim: Evaluation of ocular complications in intraoral anesthesia. Materials and Methods: It was a prospective study involving 2,400 patients undergoing different dental procedures that were performed under intraoral local anesthesia over a 12-month period. There was a thorough ocular evaluation of all patients by ophthalmologist before and after the administration of intraoral local anesthesia. Results: There were different types of ocular complications reported including accommodation disturbance, amaurosis, diplopia, enophthalmos, miosis, mydriasis, ophthalmoplegia, and ptosis. The most common ocular complication was diplopia contributing 40.1% of all ocular complications. It was followed by ptosis (16.9%), mydriasis (14.9%), and amaourosis (13.2%). Conclusion: The most common ocular complication in intraoral local anesthesia was diplopia.